Specialization for underwater hearing by the tympanic middle ear of the turtle, Trachemys scripta elegans - Christensen-Dalsgaar, J.; Brandt, C.; Willis, K.; Christensen, C.; Ketten, Darlene; Edds-Walton, P.; Fay, R.; Madsen, P.; Carr, C. (The Royal Society Publishing, 2012)
Turtles, like other amphibious animals, face a trade-off between terrestrial and aquatic hearing.We used laser vibrometry and auditory brainstem responses to measure their sensitivity to vibration stimuli and to airborne versus underwater sound. Turtles aremost sensitive to sound underwater, and their sensitivity depends on the large middle ear, which has a compliant tympanic disc attached to the columella. Behind the disc, the middle ear is a large air-filled cavity with a volume of approximately 0.5 ml and a resonance frequency of approximately 500 Hz underwater. Laser vibrometry measurements underwater showed peak vibrations at 500- 600 Hz with a maximum of 300 µm s -1 Pa -1, approximately 100 times more than the surrounding water. In air, the auditory brainstem response audiogram showed a best sensitivity to sound of 300-500 Hz. Audiograms before and after removing the skin covering reveal that the cartilaginous tympanic disc shows unchanged sensitivity, indicating that the tympanic disc, and not the overlying skin, is the key sound receiver. If air and water thresholds are compared in terms of sound intensity, thresholds in water are approximately 20-30 dB lower than in air. Therefore, this tympanic ear is specialized for underwater hearing, most probably because sound-induced pulsations of the air in the middle ear cavity drive the tympanic disc.